Exon splicing analysis of intronic variants in multigene cancer panel testing for hereditary breast/ovarian cancer - Ryu, Jin‐Sun (Cancer Sci, 2020)
The use of multigene panel testing for patients with a predisposition to breast/ovarian cancer is increasing as the identification of variants is useful for diagnosis and disease management. We identified pathogenic and likely pathogenic (P/LP) variants of high‐and moderate‐risk genes using a 23‐gene germline cancer panel in 518 patients with hereditary breast and ovarian cancers (HBOC). The frequency of P/LP variants was 12.4% (64/518) for high‐ and moderate‐penetrant genes, namely, BRCA2 (5.6%), BRCA1 (3.3%), CHEK2 (1.2%), MUTYH (0.8%), PALB2 (0.8%), MLH1 (0.4%), ATM (0.4%), BRIP1 (0.4%), TP53 (0.2%), and PMS2 (0.2%). Five patients possessed two P/LP variants in BRCA1/2 and other genes. We also compared the results from in silico splicing predictive tools and exon splicing patterns from patient samples by analyzing RT‐PCR product sequences in six P/LP intronic variants and two intronic variants of unknown significance (VUS). Altered transcriptional fragments were detected for P/LP intronic variants in BRCA1, BRIP1, CHEK2, PARB2, and PMS2. Notably, we identified an in‐frame deletion of the BRCA1 C‐terminal (BRCT) domain by exon skipping in BRCA1 c.5152+6T>C—as known VUS—indicating a risk for HBOC. Thus, exon splicing analysis can improve the identification of veiled intronic variants that would aid decision making and determination of hereditary cancer risk.